Learning mode misfits in policy learning: typology, case study and lessons learnt. - Möck, Malte; Feindt, Peter H. (Journal of European Public Policy, 2024)
Research on policy learning has shown that actors can learn in inadequate modes. To better understand policy learning failures and possible remedies, we ask how and why inadequate learning environments occur and how they can be changed. Building on the varieties of learning approach, we distinguish between perceived and functional actor certification and problem tractability. On this basis, we introduce a typology of learning mode misfits and indicative adjustments and revisit previous case studies from this perspective. We then apply the concept to a case of policy learning in a socio-technical transition, arguing that learning environments in socio-technical transitions tend to overvalue actor certification and problem tractability and require recalibration towards reflexivity. Assessing the effects of participatory co-creation interventions on technology development in precision grassland farming in two living labs in Germany, we provide evidence that decentral arenas and participatory experimentation facilitate learning by coequal actors scrutinising problems.